Working with human nature to achieve sustainability: Exploring constraints and opportunities. (1st April 2017) - Kopnina, Helen
Abstract: Sustainable production is often limited by structural factors such as industrial development, neoliberal democracy, growing population and globalization of consumer culture. Drawing on the work of some theorists linking unsustainability to universal psychological propensities, this article discusses sustainable production in relation to human nature. Human nature is understood here as complex cross-cultural and historically consistent psychological traits or universal physiological predispositions that result in the largely shared repertoire of human behavior. It is posited here that these traits, when combined with specific conditions of industrial development result in unsustainable behaviors. This article explores the relationship between human population and sustainability, human nature and culture as well as human nature and environment, and between human nature and sustainability. Recommendations focus on how sustainability efforts can take advantage of some of our natural tendencies, and mitigate others in order to provide strategic solutions to unsustainable practices. Highlights: This article links structural constraints to sustainability to human nature. Human nature is understood as cross-cultural and historically consistent psychological traits. These traits, when combined with specific cultural conditions, result in unsustainable behaviors. The relationship between human nature and culture, and between human nature and sustainability are explored. Policies that take advantage of some of our natural tendencies, and mitigate others are highlighted.